Rare Alleles and Signatures of Selection on the Immunodominant Domains of Pfs230 and Pfs48/45 in Malaria Parasites From Western Kenya - Ochwedo, Kevin O.; Ariri, Fredrick O.; Otambo, Wilfred O.; Magomere, Edwin O.; Debrah, Isaiah; Onyango, Shirley A.; Orondo, Pauline W.; Atieli, Harrysone E.; Ogolla, Sidney O.; Otieno, Antony C. A.; Mukabana, Wolfgang R.; Githeko, Andrew K.; et al. (Frontiers in Genetics, 2022)
Background: Malaria elimination and eradication efforts can be advanced by including transmission-blocking or reducing vaccines (TBVs) alongside existing interventions. Key TBV candidates, such as Pfs230 domain 1 and Pfs48/45 domain 3, should be genetically stable to avoid developing ineffective vaccines due to antigenic polymorphisms. We evaluated genetic polymorphism and temporal stability of Pfs230 domain 1 and Pfs48/45 domain 3 in Plasmodium falciparum parasites from western Kenya. Methods: Dry blood spots on filter paper were collected from febrile malaria patients reporting to community health facilities in endemic areas of Homa Bay and Kisumu Counties and an epidemic-prone area of Kisii County in 2018 and 2019. Plasmodium speciation was performed using eluted DNA and real-time PCR. Amplification of the target domains of the two Pfs genes was performed on P. falciparum positive samples. We sequenced Pfs230 domain 1 on 156 clinical isolates and Pfs48/45 domain 3 on 118 clinical isolates to infer the levels of genetic variability, signatures of selection, genetic diversity indices and perform other evolutionary analyses. Results: Pfs230 domain 1 had low nucleotide diversity (π=0.15×10-2) with slight variation per study site. Six polymorphic sites with nonsynonymous mutations and eight haplotypes were discovered. I539T was a novel variant, whereas G605S was nearing fixation. Pfs48/45 domain 3 had a low π (0.063×10-2), high conservation index, and three segregating sites, resulting in nonsynonymous mutation and four haplotypes. Some loci of Pfs230 D1 were in positive or negative linkage disequilibrium, had negative or positive selection signatures, and others (1813, 1955) and (1813, 1983) had a history of recombination. Mutated loci pairs in Pfs48/45 domain 3 had negative linkage disequilibrium, and some had negative and positive Tajima's D values with no history of recombination events. Conclusion: The two transmission blocking vaccine candidates have low nucleotide diversity, a small number of zone-specific variants, high nucleotide conservation index, and high frequency of rare alleles. With the near fixation a polymorphic site and the proximity of mutated codons to antibody binding epitopes, it will be necessary to continue monitoring sequence modifications of these domains when designing TBVs that include Pfs230 and Pfs48/45 antigens.